2015
DOI: 10.1002/macp.201500196
|View full text |Cite
|
Sign up to set email alerts
|

Nanohybrid Polymeric Nucleating Agents: In Situ Decorated Carbon Nanotubes and Serial Nucleation Behaviors in a Melt‐Miscible Crystalline/Crystalline Blend

Abstract: Polymer carbon nanotube (PCN) nanocomposites based on a melt‐miscible poly(oxymethylene)/poly(l‐lactic acid) (POM/PLLA) blend and a trace of multiwalled carbon nanotubes (MWCNTs) have been prepared by simple melt‐mixing. The crystallization behaviors of the ternary poly­mer–CNT nanocomposites (t‐PCNs) have been investigated. It is found that MWCNTs first nucleate POM selectively to yield novel “mace‐like” hybrid structure crystals. The “mace‐like” hybrid POM crystals subsequently serve as highly efficient poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Moreover, the interfaces can play a role of mold wall and enlarge the shearing effect. The nucleation easily generates in the interface, forming the oriented interfacial crystals. , It is noted that the formation of interfacial crystals is reported to improve interfacial adhesions and prevent the slippage of molecular chains.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the interfaces can play a role of mold wall and enlarge the shearing effect. The nucleation easily generates in the interface, forming the oriented interfacial crystals. , It is noted that the formation of interfacial crystals is reported to improve interfacial adhesions and prevent the slippage of molecular chains.…”
Section: Resultsmentioning
confidence: 99%
“…Third, the POM/0.9MWCNT composites exhibited higher crystallization speed than that of the PLLA/0.9MWCNT composites, suggesting that the POM crystallization happened first and then followed the PLLA crystallization in the PLLA/POM/MWCNT composites. It has been reported that POM first crystallized on the surface of MWCNTs to form hybrid structure crystals which subsequently served as nucleating agents for PLLA crystallization . As a result, the MWCNTs were probably surrounded by POM and PLLA crystallites which was disadvantageous for the electron transport among MWCNTs.…”
Section: Resultsmentioning
confidence: 99%
“…Although the compatible polymers could overcome this disadvantage, it was hard to control distribution of conductive fillers in compatible polymer blends. Poly­(oxymethylene) (POM), which is miscible with PLLA, was used to modify the properties of PLLA. , However, there was similar distribution of MWCNTs in PLLA, POM, and PLLA/POM blends. , Fortunately, the effects of single-walled carbon nanotube (SWCNT) concentration and PLLA crystallinity on conductivity of PLLA/SWCNT composites have been reported . Furthermore, the crystallinity of PLLA could be tuned in a wide range (0–50%), which could greatly help to reconstruct the MWCNT networks in the composites. …”
Section: Introductionmentioning
confidence: 99%